2022
DOI: 10.3390/healthcare10040626
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Predictors of Mental Ill Health in Esport Competitors

Abstract: Few research studies have examined the predictors of mental ill health in esports. This study addresses that gap by investigating stressors, sleep, burnout, social phobia anxiety and mental ill health in esport athletes. An online survey was disseminated to competitive student esport athletes (n = 313) residing in the UK. The survey included measures of stressors resulting from competing in esports, sleep quality, burnout, and social phobia, as well as outcome measures of mental ill health. Hierarchical regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…Specifically, current approaches to training are generally perceived by players to be suboptimal in terms of effectiveness, and in some cases, appear to be detrimental to player health and wellbeing. This theme appears to corroborate media reports of the negative psychological consequences associated with the prevailing grind culture in esports (Khan, 2020;Kou, 2020) and echoes findings from recent research on burnout and mental ill-health in esports (Smith et al, 2022). Players often expressed frustration and that they felt hampered by the inability to engage in deliberate practice due to the technical constraints of League of Legends (e.g., not being able to recreate a game state and replay/rehearse scenarios).…”
Section: -Chrissupporting
confidence: 83%
See 1 more Smart Citation
“…Specifically, current approaches to training are generally perceived by players to be suboptimal in terms of effectiveness, and in some cases, appear to be detrimental to player health and wellbeing. This theme appears to corroborate media reports of the negative psychological consequences associated with the prevailing grind culture in esports (Khan, 2020;Kou, 2020) and echoes findings from recent research on burnout and mental ill-health in esports (Smith et al, 2022). Players often expressed frustration and that they felt hampered by the inability to engage in deliberate practice due to the technical constraints of League of Legends (e.g., not being able to recreate a game state and replay/rehearse scenarios).…”
Section: -Chrissupporting
confidence: 83%
“…A recent high-profile example of this is the case of professional player "Doublelift," who quit League of Legends in part due to feelings of burnout associated with grinding games (Bosch, 2021). Indeed, preliminary research by Smith et al (2022) investigated university-level esports competitors and found that specific categories of stressors (e.g., game-specific uncertainty) predicted subcomponents of burnout, specifically a reduced sense of accomplishment and exhaustion, with the same burnout subcomponents predicting measures of mental ill health. While detailed examination of grind culture in esports is missing, it is evident in other domains and broadly encapsulates an approach in which work is heavily prioritized over other aspects of one's life (Løvestam, 2019).…”
mentioning
confidence: 99%
“…It is surprising that many perceive the concept of esports being an officially recognized sport as subversive (Jonasson & Thiborg, 2010), with differences only appearing to be in the competitive environment (real world vs. cyberspace; Chae & Kang, 2011;Pizzo et al, 2018). The expansion of research has provided the field with early insight into the impact of esports performance on individual psychophysiology (Leis & Lautenbach, 2020), the influence of cognition on performance (Pedraza-Ramirez et al, 2020), and the testing of our current theoretical understandings (Pluss et al, 2019) as well as providing direction for practitioners to generate future interventions (García-Lanzo et al, 2020;Poulus et al, 2020;Smith et al, 2022;Trotter et al, 2020). Nonetheless, a fundamental question that has been overlooked is what are the indicators of individual performance?…”
mentioning
confidence: 99%
“…Esports are a really competitive sector, and it requires hours and hours of training to achieve great performances in tournaments. This implies that there might the need to further investigate how constructs such as self-esteem [155], work-related stress [156], burnout [156], or general mattering [157] might be related to gaming motivation in pursuing this type of work; (e) can be useful to build a possible future questionnaire that tries to integrate most of the gaming motivation found. It reported most of the existent instruments (ad hoc instruments included) in literature right now to measure gaming motivation and thus giving an overview of all the gaming motivation thought and investigated as a whole.…”
Section: Discussionmentioning
confidence: 99%